Self-Awareness, Temporality, and Alterity
V, 243 p.
Keywords: Focusing on the topics of self-awareness, temporality, and alterity, this anthology contains contributions by prominent phenomenologists from Germany, Belgium, France, Japan, USA, Canada and Denmark, all addressing questions very much in the center of current phenomenological debate. What is the relation between the self and the Other? How are self-awareness and intentionality intertwined? To what extent do the temporality and corporeality of subjectivity contain a dimension of alterity? How should one account for the intersubjectivity, interculturality and historicity of the subject? These questions are not only of relevance for phenomenologists, but for anybody coming from disciplines influenced by phenomenological methodology, such as sociology, psychology, psychiatry and anthropology.